2018
DOI: 10.1016/j.jcta.2017.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Cumulants for finite free convolution

Abstract: In this paper we define cumulants for finite free convolution. We give a moment-cumulant formula and show that these cumulants satisfy desired properties: they are additive with respect to finite free convolution and they approach free cumulants as the dimension goes to infinity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…Moreover, when ( ) = ( − 1) , the second equation in Theorem 1.2 recovers the rst-order asymptotics of proven in [AP18], namely…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Moreover, when ( ) = ( − 1) , the second equation in Theorem 1.2 recovers the rst-order asymptotics of proven in [AP18], namely…”
Section: Introductionmentioning
confidence: 54%
“…Of greatest relevance to this paper is the combinatorial approach, based on cumulants, for the nite free additive convolution that was introduced by Arizmendi and Perales [AP18]. These nite free cumulants approach free cumulants as goes to in nity and share many of their properties.…”
Section: Introductionmentioning
confidence: 99%
“…Following the definitions in this paper, [10,11] have shown that by taking appropriate limits our finite free convolutions yield the standard free convolutions in free probability theory. Thus, expected characteristic polynomials provide an alternative "discretization" of free convolutions from the typical one involving random matrices.…”
Section: Motivation and Related Resultsmentioning
confidence: 99%
“…The connection was formalized in [12], where it was shown that the inequalities derived for two of the convolutions studied in [13] -the symmetric additive and multiplicative convolutionsconverge to the R-and S-transform identities of free probability (respectively). Since the release of [12], a number of advances have been made in understanding the relationship between free probability and polynomial convolutions, most notably the work of Arizmendi and Perales [1] in developing a combinatorial framework for finite free probability using finite free cumulants (the approach in [12] is primarily analytic).…”
Section: Introductionmentioning
confidence: 99%